Konstruksi gender dalam problematika childfree di sosial media Twitter - Nursyamsiah Mingkase; Inayah Rohmaniyah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Women's roles and feminine identities have historically and traditionally been built around motherhood. However, in recent years there has been a growing trend of childfree (without children) educating people about not parenting as a legitimate life choice through qualitative methods with virtual ethnographic studies. Analyzing Twitter tweets using the social construction theory of Peter L. Berger and Thomas Luckmann through a gender perspective, this paper aims to review gender construction in childfree problems where this choice is still considered taboo in the public sphere. Being Childfree allows having a positive identity oneself as an autonomous, rational, and responsible decision-maker. At the same time, rejecting that choice allows someone who cannot choose child-free (for various reasons) to have a flawless identity regarding deviations from the norm of parenthood. Although childfree is still only known in Indonesia as a whole or a broader context, childfree has been practiced by several people in a private space. However, this choice is against the culture of society where the family is considered an essential component in the life cycle; many do not feel the need or do not dare to speak up. Not only non-natural differences, gender construction that places women's nature at the biological level is also problematic. The nature of women who have a uterus is required to function correctly so that child-free decisions are considered deviant and abnormal.